Biodiesel from fish waste oil: synthesis via supercritical methanol and thermodynamic optimization. Issue 2 (22nd April 2021) - Espootin, Simin; Sameti, Mohammad; Zaker, Sahar
Abstract: This study evaluates the potential of local fish waste oil as a feedstock for biodiesel via supercritical methanol transesterification (SCMT). Hexane was used as a cosolvent and the transesterification reaction was carried out in a continuous reactor under supercritical conditions. The response surface methodology (RSM) method was applied to analyse the effect of four independent variables, including the weight ratio of methanol to fish-waste oil ( W ), the reaction temperature ( T ), the pressure ( P ) and the feed flow rate ( F ), on the yield of the biodiesel production in supercritical methanol. According to the calculated optimal operating condition for the RSM, the values of W (22.3 weight ratio of methanol to fish waste oil), T (270°C), P (112.7 bar) and F (2.0 mL min –1 ) were achieved. Under the optimum conditions, the highest yield was estimated to be 94.6% (g/g). The obtained yield was found to be close to the theoretical yield (95.2%). This value suggests that the proposed strategy has a promising potential in the production of biodiesel fuel. Abstract : This study evaluates the potential of waste fish oil as a feedstock for biodiesel via supercritical methanol transesterification. Under the optimum conditions, the highest yield was estimated to be 94.6% (g/g), close to the theoretical yield (95.2%), which suggests the proposed strategy is promising potential for the production of biodiesel. Graphical Abstract: